AN ANALYSIS ON 6TH SEMESTER STUDENTS’ TOEFL EXPERIENCE AT ENGLISH DEPARTMENT OF TEACHERS TRAINING AND EDUCATION FACULTY OF PASIR PENGARAIAN UNIVERSITY - Antoni, Rivi (Universitas Pasir Pengaraian, 2014)
The main problems faced on this research are most of the students do not have a good preparation on following a test of English as a foreign language(TOEFL) and they are also poor in English skills. Purposes of this research are to explain how students’ experiences at TOEFL test and what difficulties are found by the students at 6th semester of English Department of Pasir PengaraianUniversity in completing the TOEFL.